High-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylester composite fiber and preparation method thereof
By combining ultra -high molecular polyethylene polyethylene and armal LCD polyfords, and using a modified technology to connect polyacrylate, it is difficult to meet the high -strength and high models and wear resistance requirements at the same time. The problem realizes high -performance thermal LCD polyford composite fiber.
Patent Information
- Application Number
- CN202411335728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The prior art is difficult to meet the high-strength, high-mode and wear resistance requirements of thermogenic liquid crystal polyarylate fibers at the same time. Especially in high-end applications such as parachutes, the material's wear resistance and strength requirements are extremely high.
By combining ultra-high molecular weight polyethylene with thermotropic liquid crystal polyarylate fiber, and using modification technology to form reaction sites on the ultra-high molecular weight polyethylene molecular chain, initiating the polymerization of phenyl acrylate, polyphenylene acrylate was successfully grafted. ester, thereby improving the binding force and overall mechanical properties of the fiber.
The high -stretch strength, stretching volume and significant increased abrasion resistance of thermal liquid crystal polyfords are achieved, and they have low dielectric constants and dielectric loss, which are suitable for multi -field applications.
Smart Images

Figure SMS_1 
Figure HDA0005058182820000011 
Figure HDA0005058182820000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance chemical fibers and relates to a high-performance thermotropic liquid crystal polymer fiber and a preparation method thereof. Background Art
[0002] Thermotropic liquid crystal polyarylate fiber occupies an important position in the high-performance fiber market due to its excellent mechanical properties and heat resistance. This fiber is not only widely used in the fields of automobiles, cables, slings, etc., but also in the field of parachutes, especially parachutes in spacecraft recovery systems, it also shows its unique value.
[0003] In order to improve the wear resistance of thermotropic liquid crystal polyarylate fibers, researchers have adopted a variety of chemical modification strategies. First, by adjusting the monomer ratio and the use of catalysts, the molecular structure of the fiber can be optimized to improve its wear resistance. For example, by increasing the molar percentage of 5-aminoindole-2-carboxylic acid, the wear resistance of the fiber can be effectively enhanced. In addition, the optimization of solid phase polycondensation reaction is also an important means to improve the wear resistance of the fiber. By reacting in an inert gas atmosphere, fiber products with higher strength and modulus can be produced.
[0004] The application of surface modification technologies, such as plasma treatment and silane coupling agent treatment, is also an effective way to improve the wear resistance of fibers. These technologies can introduce active groups on the fiber surface, enhance the adhesion between the fiber and the matrix, and thus improve the wear resistance. At the same time, the addition of inorganic fillers, such as glass fiber, boron nitride fiber, etc., can also significantly improve the wear resistance of fibers.
[0005] Heat treatment is another key step to improve the wear resistance of fibers. By performing relaxation heat setting in a nitrogen atmosphere, the crystallinity and mechanical properties of the fibers can be improved, thereby enhancing the wear resistance. In addition, the application of ultraviolet radiation grafting modification technology can also effectively improve the wear resistance of fibers by introducing active groups such as acrylic acid on the fiber surface.
[0006] In the field of parachutes, the wear resistance of thermotropic liquid crystal polyarylate fibers is particularly important. The parachutes of spacecraft recovery systems need to withstand extreme mechanical loads and environmental conditions, so there are extremely high requirements for the wear resistance and strength of the materials. Through the above-mentioned chemical modification method, the performance of thermotropic liquid crystal polyarylate fibers has been significantly improved, enabling them to play an important role in key applications such as parachutes (Chinese patent CN 111038707 B).
[0007] In summary, the wear resistance of thermotropic liquid crystal polyarylate fibers has been effectively improved through chemical modification, which not only enhances its application potential in traditional fields, but also provides a solid foundation for its development in high-end application fields such as spacecraft recovery systems. With the continuous advancement of materials science, the performance of thermotropic liquid crystal polyarylate fibers will be further optimized and its application range will continue to expand.
[0008] On the other hand, ultra-high molecular weight polyethylene (UHMWPE) and its fibers are well known for their excellent wear resistance, impact resistance, low friction coefficient and good chemical stability, and are widely used in multiple industries. UHMWPE fiber has a specific strength that is 15 times that of steel, and has ultra-high strength, ultra-high modulus, low density and excellent chemical corrosion resistance, which makes it ideal in areas such as bulletproof, stab-proof security protection materials and high-performance lightweight composite materials. In terms of wear resistance, UHMWPE fiber performs well, and its wear resistance is better than many other materials, including POM (polyacetal), fluororesins and PA66 nylon. The wear resistance of this material makes it very suitable for high-wear applications such as pipes, bushings, shafts, containers, etc. The wear resistance of UHMWPE increases with the increase of molecular weight, which allows it to replace metal in applications requiring high wear resistance, while also having the advantage of lightweight. Surface modification technology of UHMWPE fibers is also constantly developing to improve its adhesion to the polymer matrix, thereby improving the mechanical properties of the composite material. These modification technologies include chemical and physical methods aimed at enhancing the activity of the fiber surface to promote bonding with the matrix. In specific areas, such as the manufacture of parachutes, the high strength and low density of UHMWPE fibers make it an ideal material choice. It can be used to make parachute ropes and fabrics, providing the required strength and durability while maintaining the overall lightness. In summary, UHMWPE and its fibers perform very well in terms of wear resistance, thanks to its unique molecular structure and physical properties.
[0009] Therefore, combining thermotropic liquid crystal polyarylate fiber with ultra-high molecular weight polyethylene is an effective way to improve the wear resistance of thermotropic liquid crystal polyarylate fiber, but there are few related reports. There are also many difficulties in the composite process of the two, such as the poor interface adhesion between ultra-high molecular weight polyethylene and thermotropic liquid crystal polyarylate, which requires targeted improvements and new process solutions.
[0010] In summary, the existing technology cannot simultaneously meet people's requirements for high strength, high modulus and wear resistance of thermotropic liquid crystal polyarylate fibers. Therefore, it is necessary to develop a thermotropic liquid crystal polyarylate fiber with high strength, high modulus and wear resistance to meet the needs of the downstream application market; and it is very necessary to develop new methods and new processes to fully combine ultra-high molecular weight polyethylene materials with thermotropic liquid crystal polyarylate materials during the development process. Summary of the invention
[0011] The purpose of the present invention is to break the bottleneck of the existing technical solutions and provide a high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber and a preparation method thereof. The present invention can be achieved by the following technical solutions:
[0012] The present invention provides a high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber having a composite structure (fiber cross-sectional structure such as Figure 1 The main components are thermotropic liquid crystal polyarylate and modified ultra-high molecular weight polyethylene. In the composite structure, the thermotropic liquid crystal polyarylate fiber accounts for 30-95 parts by weight, and the modified ultra-high molecular weight polyethylene resin accounts for 5-80 parts by weight.
[0013] Preferably, the high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber, wherein the thermotropic liquid crystal polyarylate fiber used has a tensile strength of 20-40 cN / dtex, a tensile modulus of 500-1000 cN / dtex, and a weight average molecular weight of the modified ultra-high molecular weight polyethylene of 1 million to 10 million.
[0014] The present invention also provides a method for preparing a high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber, which specifically comprises the following steps:
[0015] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a certain proportion to obtain a modified solution. Ultra-high molecular weight polyethylene powder is added to the modified solution, high-purity argon gas is introduced and stirred for a period of time to obtain a solid-liquid mixture.
[0016] Step 2: Use an ultraviolet lamp with a wavelength of 253nm to irradiate the solid-liquid mixture of step 2 for a period of time, continue to stir and continuously introduce high-purity argon during the irradiation process, and control the temperature of the solid-liquid mixture within a certain range. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at a certain temperature to obtain a modified ultra-high molecular weight polyethylene powder.
[0017] Step 3: Mix the modified ultra-high molecular weight polyethylene powder with decalin, and mechanically stir for a period of time at a certain temperature to fully dissolve the modified ultra-high molecular weight polyethylene to obtain a modified ultra-high molecular weight polyethylene / decalin solution with a certain mass fraction concentration.
[0018] Step 4: preheating the thermotropic liquid crystal polyarylate fibers (including thermotropic liquid crystal polyarylate monofilaments and thermotropic liquid crystal polyarylate multifilaments) in air at a certain temperature, and then coating the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fibers by a screw extruder at a certain temperature, and then passing through a high-temperature oven to evaporate the decalin to obtain the thermotropic liquid crystal polyarylate composite fibers.
[0019] Preferably, in step 1, the chemical structures of (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (hereinafter referred to as benzophenone compound 1) and thioperoxydicarbonic acid ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (hereinafter referred to as disulfide compound 2) are as follows: Figure 2 As shown, the molar ratio of benzophenone compound 1, disulfide compound 2 and phenyl acrylate is 1:1:(100-300); the weight average molecular weight of the ultra-high molecular weight polyethylene powder in step 1 is between 1 million and 8 million; the purity of argon is greater than 99.999%; the amount of argon introduced is 10-2000 ml / min; the mass ratio of ultra-high molecular weight polyethylene to phenyl acrylate is 1:(0.1-50), and the stirring and nitrogen passing time are the same, which is 5-60 minutes.
[0020] Preferably, in step 2, the amount of argon gas introduced is 10-2000 ml / min, the temperature of the solid-liquid mixture is controlled in the range of 10 to 60 degrees Celsius, and the ultraviolet lamp irradiation time is 3 to 48 hours. During the drying process, the oven temperature is 40-80 degrees, and the drying time is 2-10 hours.
[0021] Preferably, in step 3, the temperature of the modified ultra-high molecular weight polyethylene powder and decalin is controlled at 60-150 degrees Celsius when they are mixed, and the mechanical stirring is 1 to 5 hours. The mass fraction concentration of the modified ultra-high molecular weight polyethylene in the obtained modified ultra-high molecular weight polyethylene / decalin solution is 0.5% to 10%.
[0022] Preferably, in step 4, the thermotropic liquid crystal polyarylate fibers (including thermotropic liquid crystal polyarylate monofilaments and thermotropic liquid crystal polyarylate multifilaments) are preheated in air at 100-150 degrees Celsius. The screw extruder is set at a temperature of 60-200 degrees Celsius, and the temperature of the high temperature oven is 100-250 degrees Celsius.
[0023] The thermotropic liquid crystal polyarylate composite fiber obtained through steps 1 to 4 of the present invention has a tensile strength higher than 24 cN / dtex, a tensile modulus higher than 800 cN / dtex, and a strength retention rate higher than 90% after rubbing 10,000 times.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: using ultra-high molecular weight polyethylene as a coating material and thermotropic liquid crystal polyarylate fiber as a core material, the wear resistance of the composite fiber as a whole can be effectively improved while retaining the original high mechanical properties; at the same time, the present invention also adopts a modification technology to chemically modify the ultra-high molecular weight polyethylene before coating, and on the ultra-high molecular weight polyethylene molecular chain, a reaction site is formed under the action of a benzophenone compound and a disulfide compound to initiate the polymerization of a monomer such as phenyl acrylate, and successfully graft polyphenyl acrylate. The ultra-high molecular weight polyethylene grafted with polyphenyl acrylate molecular chains has a similar chemical structure to polyarylate, the main component of thermotropic liquid crystal polyarylate fiber, and compared with unmodified ultra-high molecular weight polyethylene materials, the method provided by the present invention can effectively improve the bonding force between ultra-high molecular weight polyethylene and thermotropic liquid crystal polyarylate fiber, and is shown in performance as having more excellent overall mechanical properties and wear resistance, and the composite fiber has a lower dielectric constant (less than or equal to 2.5) and dielectric loss (less than or equal to 0.005).
[0025] The thermotropic liquid crystal polyarylate composite fiber of the present invention can be processed according to the product property requirements, and various other additives can be added during the composite process, such as antioxidants, antistatic agents, flame retardants, pigments, glass fibers, inorganic powders, etc. Suitable application fields include fishing lines, cables, arresting cables, parachutes, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the cross-sectional structure of a melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber composite yarn.
[0027] Figure 2 It is the chemical structural formula of benzophenone compound 1 and disulfide compound 2. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0029] Example 1
[0030] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:100 to obtain a modified solution. Ultra-high molecular weight polyethylene powder with a weight average molecular weight of 2 million is added to the modified solution, and the mass ratio of ultra-high molecular weight polyethylene to phenyl acrylate is 1:10. Argon gas with a purity greater than 99.999% is introduced at a rate of 200 ml / min, and stirred for 30 minutes to obtain a solid-liquid mixture.
[0031] Step 2: Use an ultraviolet lamp with a wavelength of 253 nm to irradiate the solid-liquid mixture of step 2 for 12 hours. During the irradiation process, continue to stir and continuously introduce high-purity argon gas, the argon introduction rate is 200 ml / min, and the temperature of the solid-liquid mixture is controlled at 20 degrees Celsius. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at 60 degrees Celsius for 3 hours to obtain a modified ultra-high molecular weight polyethylene powder.
[0032] Step 3: Mix the modified ultra-high molecular weight polyethylene powder with decalin, and mechanically stir at 80 degrees Celsius for 2 hours to fully dissolve the modified ultra-high molecular weight polyethylene, thereby obtaining a modified ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 2%.
[0033] Step 4: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 110 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 110 degrees Celsius, and then pass through a high-temperature oven at 150 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0034] In the prepared composite fiber, the weight of the thermotropic liquid crystal polyarylate accounts for 78 parts, and the weight of the modified ultra-high molecular weight polyethylene resin accounts for 22 parts.
[0035] Example 2
[0036] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:150 to obtain a modified solution. Ultra-high molecular weight polyethylene powder with a weight average molecular weight of 2.5 million is added to the modified solution, and the mass ratio of ultra-high molecular weight polyethylene to phenyl acrylate is 1:50. Argon gas with a purity greater than 99.999% is introduced at a rate of 500 ml / min, and stirred for 40 minutes to obtain a solid-liquid mixture.
[0037] Step 2: Use an ultraviolet lamp with a wavelength of 253 nm to irradiate the solid-liquid mixture of step 2 for 18 hours. During the irradiation process, continue to stir and continuously introduce high-purity argon gas, the argon introduction rate is 500 ml / min, and the temperature of the solid-liquid mixture is controlled at 25 degrees Celsius. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at 70 degrees Celsius for 5 hours to obtain a modified ultra-high molecular weight polyethylene powder.
[0038] Step 3: Mix the modified ultra-high molecular weight polyethylene powder with decalin, and mechanically stir at 90 degrees Celsius for 2.5 hours to fully dissolve the modified ultra-high molecular weight polyethylene, thereby obtaining a modified ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 3%.
[0039] Step 4: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 115 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 120 degrees Celsius, and then pass through a high-temperature oven at 155 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0040] In the prepared composite fiber, the weight of the thermotropic liquid crystal polyarylate accounts for 82 parts, and the weight of the modified ultra-high molecular weight polyethylene resin accounts for 18 parts.
[0041] Example 3
[0042] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:200 to obtain a modified solution. Ultra-high molecular weight polyethylene powder with a weight average molecular weight of 3 million is added to the modified solution, and the mass ratio of ultra-high molecular weight polyethylene to phenyl acrylate is 1:80. Argon gas with a purity greater than 99.999% is introduced at a rate of 200 ml / min, and stirred for 30 minutes to obtain a solid-liquid mixture.
[0043] Step 2: Use an ultraviolet lamp with a wavelength of 253 nm to irradiate the solid-liquid mixture of step 2 for 12 hours. During the irradiation process, continue to stir and continuously introduce high-purity argon gas, the argon introduction rate is 700 ml / min, and the temperature of the solid-liquid mixture is controlled at 20 degrees Celsius. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at 80 degrees Celsius for 3 hours to obtain a modified ultrahigh molecular weight polyethylene powder.
[0044] Step 3: Mix the modified ultra-high molecular weight polyethylene powder with decalin, and mechanically stir at 100 degrees Celsius for 3 hours to fully dissolve the modified ultra-high molecular weight polyethylene, thereby obtaining a modified ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 2.5%.
[0045] Step 4: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 115 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 125 degrees Celsius, and then pass through a high-temperature oven at 160 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0046] The prepared composite fiber contains 85 parts by weight of thermotropic liquid crystal polyarylate and 15 parts by weight of modified ultrahigh molecular weight polyethylene resin.
[0047] Example 4
[0048] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:100 to obtain a modified solution. Ultra-high molecular weight polyethylene powder with a weight average molecular weight of 5 million is added to the modified solution, and the mass ratio of ultra-high molecular weight polyethylene to phenyl acrylate is 1:150. Argon gas with a purity greater than 99.999% is introduced at a rate of 500 ml / min, and stirred for 55 minutes to obtain a solid-liquid mixture.
[0049] Step 2: Use an ultraviolet lamp with a wavelength of 253 nm to irradiate the solid-liquid mixture of step 2 for 20 hours. During the irradiation process, continue to stir and continuously introduce high-purity argon gas, the argon introduction rate is 1000 ml / min, and the temperature of the solid-liquid mixture is controlled at 23 degrees Celsius. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at 65 degrees Celsius for 6 hours to obtain a modified ultra-high molecular weight polyethylene powder.
[0050] Step 3: Mix the modified ultra-high molecular weight polyethylene powder with decalin, and mechanically stir at 110 degrees Celsius for 3 hours to fully dissolve the modified ultra-high molecular weight polyethylene, thereby obtaining a modified ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 3%.
[0051] Step 4: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 110 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 115 degrees Celsius, and then pass through a high-temperature oven at 150 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0052] The prepared composite fiber contains 89 parts by weight of thermotropic liquid crystal polyarylate and 11 parts by weight of modified ultrahigh molecular weight polyethylene resin.
[0053] Comparative Example 1
[0054] Step 1: Mix ultra-high molecular weight polyethylene powder with a weight average molecular weight of 2 million with decalin, and mechanically stir at 80 degrees Celsius for 2 hours to fully dissolve the ultra-high molecular weight polyethylene to obtain an ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 2%.
[0055] Step 2: preheat the thermotropic liquid crystal polyarylate fiber in air at 110 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 110 degrees Celsius, and then pass through a high-temperature oven at 150 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0056] In the prepared composite fiber, the weight of the thermotropic liquid crystal polyarylate accounts for 85 parts, and the weight of the ultra-high molecular weight polyethylene resin accounts for 15 parts.
[0057] Comparative Example 2
[0058] Step 1: Mix ultra-high molecular weight polyethylene powder with a weight average molecular weight of 5 million with decalin, and mechanically stir at 110 degrees Celsius for 3 hours to fully dissolve the ultra-high molecular weight polyethylene to obtain an ultra-high molecular weight polyethylene / decalin solution with a mass concentration of 3%.
[0059] Step 2: preheat the thermotropic liquid crystal polyarylate fiber in air at 110 degrees Celsius, and then use a screw extruder to coat the modified ultra-high molecular weight polyethylene / decalin solution in step 3 on the surface of the thermotropic liquid crystal polyarylate fiber at 115 degrees Celsius, and then pass through a high-temperature oven at 150 degrees to evaporate the decalin to obtain a thermotropic liquid crystal polyarylate composite fiber.
[0060] In the prepared composite fiber, the weight of the thermotropic liquid crystal polyarylate accounts for 89 parts, and the weight of the ultra-high molecular weight polyethylene resin accounts for 11 parts.
[0061] The relevant material properties of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.
[0062] Table 1
[0063]
[0064] Note: The tensile strength, tensile modulus and dielectric constant in the table are the average values of 20 samples measured under the same processing technology.
[0065] As can be seen from the above table, the tensile strength, tensile modulus and wear resistance of the high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber prepared by the present invention are significantly improved compared with the products obtained by the conventional method, especially the wear resistance index is significantly improved, indicating that the method of the present invention can effectively improve the performance of the fiber.
Claims
1. A high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber, characterized in that: The fiber is mainly composed of thermotropic liquid crystal polyarylate and modified ultra-high molecular weight polyethylene, wherein the thermotropic liquid crystal polyarylate fiber accounts for 30-95 parts by weight and the modified ultra-high molecular weight polyethylene accounts for 5-80 parts by weight; The method for preparing a high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber comprises: step (1) premixing a benzophenone compound, a disulfide compound and phenyl acrylate to obtain a modified solution, and then mixing it with ultra-high molecular weight polyethylene powder; step (2) modifying it in argon gas under ultraviolet light irradiation to obtain a modified ultra-high molecular weight polyethylene; step (3) dissolving the modified ultra-high molecular weight polyethylene in decalin to obtain a modified ultra-high molecular weight polyethylene / decalin solution; step (4) using a screw extruder to compound it with the preheated thermotropic liquid crystal polyarylate fiber, and then heating it in an oven to obtain a high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber.
2. The high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber and its preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of the benzophenone compound 1, the disulfide compound 2 and phenyl acrylate is 1:1:(100-300), the mass ratio of the ultra-high molecular weight polyethylene to phenyl acrylate is 1:(0.1-50), and the weight average molecular weight of the ultra-high molecular weight polyethylene powder is between 1 million and 8 million.
3. The high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber and its preparation method according to claim 1, characterized in that: The ultraviolet lamp irradiation time in step (2) is 3 to 48 hours.
4. The high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber and its preparation method according to claim 1, characterized in that: In the step (3), the mass fraction concentration of the modified ultra-high molecular weight polyethylene is 0.5% to 10%.
5. The high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber and its preparation method according to claim 1, characterized in that: The thermotropic liquid crystal polyarylate fibers described in step (4) include thermotropic liquid crystal polyarylate monofilaments and thermotropic liquid crystal polyarylate multifilaments, which are preheated in air at 100-150 degrees Celsius, the screw extruder is set at a temperature of 60-200 degrees Celsius, and the oven is set at a temperature of 100-250 degrees Celsius.
6. The high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber according to claim 1, characterized in that: The obtained high-strength, high-modulus and wear-resistant thermotropic liquid crystal polyarylate composite fiber has a tensile strength higher than 24 cN / dtex, a tensile modulus higher than 800 cN / dtex, a strength retention rate higher than 90% after 10,000 frictions, a dielectric constant less than or equal to 2.5, and a dielectric loss less than or equal to 0.005.
Citation Information
Patent Citations
A polyarylate silk main umbrella for use in deceleration parachutes
CN111038707B
Composite material for preparing intermediate strength fibers and quick forming method and application hereof
CN109233062A
Selly spun polyethylene / thermotropic liquid crystal composite fiber and its preparing method
CN1641082A
Reinforced aromatic polycarbonate resin composition
JP2006249286A
Abrasion resistant fabric
US20110111200A1